On the uniqueness of extension and unique best approximation in the dual of an asymmetric normed linear space - Mustăţa, Costică (Rev. Anal. Numér. Théor. Approx., 2003)
A well known result of R. R. Phelps (1960) asserts that in order that every linear continuous functional, defined on a subspace \(Y\) of a real normed space \(X\), have a unique norm preserving extension it is necessary and sufficient that its annihilator \(Y^\bot\) be a Chebyshevian subspace of \(X^*\). The aim of this note is to show that this result holds also in the case of spaces with asymmetric norm.